2005
DOI: 10.1038/sj.eye.6701779
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity in South Africans at a tertiary hospital: a prospective study

Abstract: Background and Objectives World Health Organization's vision 20/20 programme has recognized retinopathy of prematurity (ROP) as an important cause of childhood blindness in industrialized and middle-income countries. While ROP is virtually nonexistent in many African countries, ROP is seen in urban areas where facilities for neonatal care exist. The aim of this study is to establish the frequency of ROP in a cohort of patients screened for ROP and to establish if current screening criteria apply to our patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…The prevalence of severe ROP was 3.2% in infants weighing <1 250 g at birth, with 4.3% requiring treatment, slightly higher than in our study. In a study in Johannesburg published in 2006, Mayet et al [5] showed a 16.3% prevalence of ROP in VLBW infants -1.6% of infants received treatment. As in other SA studies, the majority of infants with ROP weighed <1 250_g and no infant weighing >1 250 g required treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of severe ROP was 3.2% in infants weighing <1 250 g at birth, with 4.3% requiring treatment, slightly higher than in our study. In a study in Johannesburg published in 2006, Mayet et al [5] showed a 16.3% prevalence of ROP in VLBW infants -1.6% of infants received treatment. As in other SA studies, the majority of infants with ROP weighed <1 250_g and no infant weighing >1 250 g required treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is significantly higher than in previous studies at GSH. [4,5] Infrastructure and resources in the healthcare facilities referring to GSH have improved in the past two decades. Additionally, surfactant therapy and non-invasive ventilation are more accessible, contributing to improved preterm (n= (n= RESEARCH survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study at Chris Hani Baragwanath Academic Hospital found the incidence to be ~17%. [10] In another study undertaken at Tygerberg Children's Hospital in Cape Town, the incidence was found to be 21.8%. [13] A study by Delport et al [14] at Kalafong Hospital, Pretoria, found the incidence of ROP to be 24.5%.…”
Section: Researchmentioning
confidence: 99%
“…In a large prospective study done at Chris Hani Baragwanath Academic Hospital to establish the frequency of ROP it was concluded that this was not the case, and the screening weight could safely be lowered to 1 250 g. [10] According to the latest ROP guidelines published in the South African Medical Journal (SAMJ), all very-low-birth-weight (VLBW) babies <1 500 g or 32 weeks' GA should be screened for ROP. [11] Screening is repeated until retinal vascularisation has reached a stage where the risk of a serious adverse outcome is considered minimal.…”
Section: Researchmentioning
confidence: 99%